Peran Orang Tua dalam Mengembangkan Kecerdasan Spiritual Anak Usia Prasekolah di PAUD Al-Muttaqin - Dewita, Erna; Maiseptian, Fadil; Thaheransyah, Thaheransyah (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2021)
Spiritual intelligence is the main potential that parents must pay attention to so that children experience good development. Parents often ignore the spiritual formation of preschool children because of the view that children of this age are only so that their spiritual formation is not a priority. The purpose of this study was to determine the role of parents in developing the spiritual intelligence of preschool children based on conceptual, social, and religious ethical aspects. The method used in this research is field research. This type of research is a case study. Selection of subjects using purposive sampling technique that is based on the need for the problem. Data collection techniques with interviews and data analysis techniques using the Miles and Huberman model. The results showed that the role of parents in developing children's religious attitudes through exemplary stories, teaching practical worship, and uswatun hasanah. To develop social religion is done by accustoming children to respect and listen to others, to respect each other, to cooperate, and to get children to forgive and apologize. Developing religious ethics for preschool children through fostering patience, sincerity, having good prejudice, thinking logically and independently.